On the syntactic basis of the study of morphology of a language - Saidova Mukhabbat Shukrullaevna (Genius Publishing Group, 2021)
The article retrospectively highlights individual forms of implementing the idea of studying morphology on a syntactic basis and gives considerations on further increasing the effectiveness of this idea when taking a course in the modern Russian literary language, and draws some conclusions from observations of the degree of understanding by students
Keywords: Linguodidactics; morphology; syntactic basis; comprehension